Current prevention and potential treatment options for dengue infection - Jasamai, Malina; Yap, Wei Boon; Sakulpanich, Aurapa; Jaleel, Azmath (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Currently, treatments for dengue infection are only symptomatic as no antiviral agents nor vaccines are available to combat this virus. Despite challenges faced by researchers, many efforts are ongoing to reduce cases of dengue infection either by targeting the vector or the virus. Vector population is monitored and reduced by using mechanical, chemical and biological controls. Chemical control is achieved either by using synthetic or natural insecticides where the latter is more preferable. In biological control, bacteria, fungi and larvivorous fish are utilised to reduce the vector population. Moreover, genes of mosquitoes are also explored to produce progenies which are sterile with low survival ability. Vaccines are among the most effective ways to prevent viral infection. Various approaches have been used and are still being explored towards producing vaccines for dengue. These include live attenuated, inactivated, recombinant subunit, nucleic acid and virus-like particles vaccines. The aim is to produce a vaccine which can target all the four serotypes of the virus. Monoclonal antibodies are widely researched on to equip the host defense mechanism against the dengue virus. Deeper understanding of the virus replication cycle warrants the development of antiviral agents which target viral proteins vital for the replication process. Bioactive compounds are also utilised in the development of antiviral agents. The importance of surveillance and supportive therapy are also discussed.